2017
DOI: 10.1037/pspp0000131
|View full text |Cite
|
Sign up to set email alerts
|

Moving on or digging deeper: Regulatory mode and interpersonal conflict resolution.

Abstract: Conflict resolution, in its most basic sense, requires movement and change between opposing motivational states. Although scholars and practitioners have long acknowledged this point, research has yet to investigate whether individual differences in the motivation for movement from state-to-state influence conflict resolution processes. Regulatory Mode Theory (RMT) describes this fundamental motivation as locomotion. RMT simultaneously describes an orthogonal motivational emphasis on assessment, a tendency for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 82 publications
2
33
0
Order By: Relevance
“…In this regard, research has found that locomotion increases the motivation to reconcile and decreases the influence on reconciliation of the feelings of negativity from the conflict. In contrast, assessment decreases the motivation to reconcile and increases the influence of the negative feelings from the conflict [ 55 ]. These forgiveness-of-others findings are consistent with what we found for self-forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, research has found that locomotion increases the motivation to reconcile and decreases the influence on reconciliation of the feelings of negativity from the conflict. In contrast, assessment decreases the motivation to reconcile and increases the influence of the negative feelings from the conflict [ 55 ]. These forgiveness-of-others findings are consistent with what we found for self-forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, at the system level, promotion (prevention) has a concern for advancement and growth (safety and security). At the strategic level, promotion (prevention) thus entails a preference for eager and risky approach (cautious and vigilant avoidance) strategies (for a similar reasoning and predominance approach regarding regulatory mode, not considered in this work, see, e.g., Higgins, Pierro, & Kruglanski, 2008;Orehek, Mauro, Kruglanski, & Van der Bles, 2012;Webb et al, 2017). 3 Using a mixed repeated measures ANOVA is a conservative means to test our hypothesis regarding the Regulatory Focus 3 Value Framing interaction, as it controls for the covariation of all 20 dependent variables (i.e., the 10 values in both frames).…”
Section: Note Smentioning
confidence: 99%
“…The predominance perspective thus creates the clearest theory‐driven predictions, as predominance determines which focus/orientation is chronically in the foreground (cf. Cesario & Higgins, ; Righetti et al, ; Webb, Coleman, Rossignac‐Milon, Tomasulo, & Higgins, ). As noted elsewhere (e.g., Higgins, ; Righetti et al, ; Webb et al, ), regulatory focus and other motivational orientations are in opposition at the system and strategic levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations